MENUJU INTEGRASI ILMU-ILMU KEISLAMAN DENGAN ILMU-ILMU UMUM (Integratif Antara Kajian Yang Bersumber Ayat-ayat Qauliyah dan Ayat-ayat Kauniyah) - Susilawati Susilawati (Lembaga Penelitian Dan Pengabdian Masyarakat Institut Agama Islam Sultan Muhammad Syafiuddin Sambas Kalimantan Barat, 2022)
The Qur'an was revealed to humans in addition to being a differentiator between right and wrong, it also guides humans to demand and develop knowledge. Since the credibility of the Church as a source of scientific information has declined, a scientific approach to science has flourished towards secular knowledge. The occurrence of the dichotomy of Islamic science with general sciences causes Islamic scientists to try to Islamize or integrate the two sciences, because if this is not done it will have a negative impact on human life. The response of Muslim scholars regarding the relationship between Islamic science and the general public has three typologies, namely: Restorationist, Reconstructionist, and Reintegration.